High utilization ratio of metal organic sources for MOCVD-derived GdYBCO films based on a narrow channel reaction chamber. (13th December 2017) - Zhao, Ruipeng; Liu, Qing; Xia, Yudong; Tang, Hao; Lu, Yuming; Cai, Chuanbing; Tao, Bowan; Li, Yanrong
Abstract: A narrow channel reaction chamber is designed in our home-made MOCVD system and applied to deposit GdYBCO films on the template of LaMnO3 /epitaxial MgO/IBAD-MgO/solution deposition planarization-Y2 O3 -buffered Hastelloy tapes. In the reaction chamber, metal organic sources are transferred from the inlet to the outlet along the direction of the tape movement. Thus, compared to the vertical injection way of metal organic sources, the residence time of metal organic sources on the surface of substrates would be extended through adopting the novel reaction chamber. Therefore, the utilization of metal organic sources, which is calculated according to the measured results of experiments, can reach 31%. Additionally, the utilization ratio of metal organic sources based on the novel reaction chamber is basically two times as much as that of the commonly used vertical injection slit shower. What is more, through adjusting the process, the critical current density of 300 nm thick GdYBCO film prepared the reel-to-reel way has reached 3.2 MA cm −2 (77 K, 0 T).